PROFIL KEMAMPUAN MEMBACA SISWA KELAS 5 SEKOLAH DASAR (SD) DAN MADRASAH IBTIDAIYAH (MI) DITINJAU DARI JENIS SEKOLAH DAN JENIS KELAMIN - Hidayah, Rifa (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
This study wanted to test the reading ability of students in grade 5 elementary school and madrasah, aged 9-11 years in terms of gender and type of school. Data collection tool tests the ability to read and the data entry student sex and type of school that consists of Elementary and MI. Research subjects amounted to 71 students from two schools, which consists of 43 elementary school students and 28 students MI. The results of data analysis showed that there was no difference between reading ability between men and women (p 0.05). In review of the types of schools that is students from elementary school and MI (p 00.5) and no difference in reading ability.Key words: Ability to read, gender, type of school